QUESTIONS ABOUT THE INSTITUTION AND TRAINING OF THE PSYCHOANALYST - Laéria Fontenele (Revista de Psicologia)
This is a conference given by Laéria Fontenele at the invitation of the psychoanalytic institution called “Lacan Salon”, based in Vancouver (Canada), on June 15, 2024, through the Zomm Meeting. On this occasion, some questions were focused on the institution and training of the analyst, originating from the author's experience as a psychoanalyst and director of the “Corpo Freudiano Escola de Psicanálise - Seção Fortaleza” since 2021. In addition, it tried to specify the way of operating that characterizes the “Corpo Freudiano Escola de Psicanálise” as an institution dedicated to the transmission of psychoanalysis based on two logical forms inherent to the two modes of organization that are currently found in psychoanalytic institutions as systematized by Diana Rabinovich.